2011
DOI: 10.1111/j.1439-0396.2011.01187.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplementation of multi‐microbe probiotic product on growth performance, apparent digestibility, cecal microbiota and small intestinal morphology of broilers

Abstract: The present study investigated the effect of inclusion of multi-microbe probiotic product on growth performance, apparent digestibility of nutrients, cecal microbiota and small intestinal morphology in broilers. Four hundred days-old Ross chicks were randomly allotted to five treatments on the basis of body weight (BW). Each treatment had four replicates of 20 chicks in each. Experimental diets were fed in two phases, starter (day 0-21) and finisher (day 22-35). Dietary treatments were; basal diet without any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
2
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 31 publications
5
29
2
6
Order By: Relevance
“…However, there were no additional beneficial effects of combining bacteriophages and probiotics. Previous studies in our laboratory on pigs and broiler reported improved intestinal morphology with dietary supplementation with fermented probiotics product (Choi et al, 2011a and2011b;Kim et al, 2012). Mourao et al (2005) reported that a decreased number of pathogenic bacteria in the gut may improve proliferation of epithelial cells to build villus and thus enhance intestinal morphology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there were no additional beneficial effects of combining bacteriophages and probiotics. Previous studies in our laboratory on pigs and broiler reported improved intestinal morphology with dietary supplementation with fermented probiotics product (Choi et al, 2011a and2011b;Kim et al, 2012). Mourao et al (2005) reported that a decreased number of pathogenic bacteria in the gut may improve proliferation of epithelial cells to build villus and thus enhance intestinal morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that supplementation with bacteriophages resulted in improved growth performance and gut health of growing pigs (Yan et al, 2012;Kim et al 2014b). Previous studies in the author's laboratory reported that the multimicrobial probiotic products had potential to improve the performance and gut health, and could be used as an alternative to antibiotic growth promoters in pigs and broilers (Choi et al, 2011b;Kim et al, 2012). Therefore, the present study was designed to investigate the effects of dietary supplementation with bacteriophage and also its combination with fermented probiotic product on growth performance, nutrient digestibility, intestinal and fecal microbiota and intestinal morphology of weanling pigs.…”
Section: Introductionmentioning
confidence: 99%
“…Awad et al (2010) have reported that villus height to crypt depth ratio increased in duodenum and ileum of chicks supplemented with Lactobacillus sp. Similarly, supplementation of multi-microbe probiotic product has been reported to cause increased villus height to crypt depth ratio in duodenum and ileum (Kim et al, 2011). It has been indicated that, increased villus height to crypt depth ratio are directly correlated with an increased epithelial turnover (Fan et al, 1997).…”
Section: Villus Height/crypt Depth Ratiomentioning
confidence: 99%
“…It has been reported that the use of a DFM containing Bacillus spp. has a positive effect on the performance and immune system of broiler chicks (Teo and Tan, 2007;Kim et al, 2012;Amerah et al, 2013a). Timmerman et al (2006) observed that chicken specific DFM preparations reduced mortality in broilers.…”
Section: Journal Of Applied Animal Nutritionmentioning
confidence: 99%